A Pathology Data Management System (PADAMS 7810) for the Interactive Storage and Retrieval of Autopsy Records) - Takahashi, M.; Masttda, M.; Isiglo, K.; Matsttmoto, T. (Methods of Information in Medicine, 1979)
An on-line system for the computer-assisted management of pathology data, calledPADAMS (Pathology Data Management System), was developed to construct a data base and to gam direct access to the up-to-date information in daily practice. It utilizes the time-sharing system (TSS) of FACOM M-190 and is operable from a terminal in the pathology department. By prompting data input the system leads the user to register cases and to form interrogations for data retrieval. Pathological and anatomical terms are automatically coded according to SNOP and decoded during output. In the absence of the term in the dictionary, the code is requested and filed so that the vocabulary is increased stepwise during operation of PADAMS. Additional subroutines can be called to read and to correct the dictionary. PADAMS was successfully tested on 100 samples of record. Further data are now being accumulated in the file.
Keywords: PADAMS; Interactive Data Management; Automatic Coding; Progressive Formation of a Dictionary; SNOP